The Development of a 2D Animation Entitled "War of Loss" to Promote Awareness of the Impacts of World War II - พิทักษ์กุล นัฐพล; บูรณ์คณัสฺ ธนากร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to design and develop a 2D animation media entitled "The War of Loss" to promote awareness of the impacts of World War II among lower secondary school students. The animation was designed to present the story through the perspective of Japanese soldiers in the Battle of Okinawa, aiming to portray the brutality, profound loss, and psychological trauma caused by the war. The sample group used in this research consisted of 30 Grade 9 students from Wat Khlong Chan School, selected via simple random sampling. The research included a quality assessment by experts and a student satisfaction evaluation using a questionnaire. The research findings revealed that: 1) The developed 2D animation successfully portrayed the severity and profound loss of World War II through the perspective of soldiers in the Battle of Okinawa. 2) Regarding awareness promotion, the media effectively stimulated the sample group’s realization of the impacts and brutality of the war at a very good level (Mean = 4.83, S.D. = 0.38). 3) The quality assessment by experts indicated that the content and media aspects were at a good level (Mean = 4.27, S.D. = 0.42 and Mean = 4.20, S.D. = 0.37, respectively). Furthermore, the overall satisfaction of the sample group was at a very good level (Mean = 4.69, S.D. = 0.49). These results demonstrate that the developed 2D animation is effective and can be appropriately utilized as supplementary learning material in history courses. However, recommendations for further development suggest improving the animation frame rate, pacing in key scenes, character background development, and the realism of sound effects to maximize the emotional communication and reach perfection.